On the sintering of solution-based silver nanoparticle thin-films for sprayed and flexible antennas. (28th September 2018) - Bobinger, Marco; Haider, Michael; Goliya, Yash; Albrecht, Andreas; Becherer, Markus; Lugli, Paolo; Rivadeneyra, Almudena; Russer, Johannes
Abstract: In this work, we report on the fabrication and characterization of sub-300 nm electrode films based on solution-processed silver nanoparticles (AgNPs). Following the deposition of the electrode material using a scalable and homogenous spray process, the films are treated with thermal or photonic sintering to promote the coalescence of the nanoparticles and in turn decrease the resistivity of the films. After sintering, a resistivity of 63 ± 13 nΩ m is achieved for the AgNP films, which is only by a factor of four larger than the literature value for bulk silver. Both post-deposition treatments show a similar performance with regard to the achieved resistivity. However, photonic sintering avoids the need for thermal annealing at substrate temperatures of 150 °C and above. In addition, the photonic sintering process can easily be embedded in a roll-to-roll process and is extremely fast with light exposure times below 3 ms. Thus, this manufacturing technique paves the way for the use of flexible substrates in electronics. As a simple and practical application, we present the use of AgNP films for antennas operating in the 5 GHz band on flexible polyethylene terephthalate substrate. An original coplanar design is employed for the fabrication of antennas with a single conductive layer that exhibit a maximum return loss and radiation of −27 dB and 95%, respectively.